2014
DOI: 10.2147/btt.s50734
|View full text |Cite
|
Sign up to set email alerts
|

Resistant mutations in CML and Ph+ALL – role of ponatinib

Abstract: In 2012, ponatinib (Iclusig®), an orally available pan-BCR-ABL tyrosine kinase inhibitor (TKI) developed by ARIAD Pharmaceuticals, Inc., was approved by the US Food and Drug Administration for use in resistant or intolerant chronic myeloid leukemia (CML) and Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ALL). Ponatinib is the only approved TKI capable of inhibiting BCR-ABL with the gatekeeper T315I kinase domain mutation, known to be the cause for 20% of resistant or relapsed CML cases. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 61 publications
(94 reference statements)
0
35
0
Order By: Relevance
“…The response rate and safety profile of T315I patients were comparable to those observed in the overall population of refractory CML and Ph+, ALL patients in ponatinib clinical trials 8. No mutation conferring resistance to Ponatinib, so far, has been identified 2,9,10. With longer follow-up and the availability of second and third generation TKIs, most clinically relevant ABL kinase mutations respond to change in TKI therapy following imatinib failure, with the majority of patients achieving durable cytogenetic and molecular responses.…”
Section: How To Proceed To Manage CML Disease After Multi-tki Failure?mentioning
confidence: 99%
“…The response rate and safety profile of T315I patients were comparable to those observed in the overall population of refractory CML and Ph+, ALL patients in ponatinib clinical trials 8. No mutation conferring resistance to Ponatinib, so far, has been identified 2,9,10. With longer follow-up and the availability of second and third generation TKIs, most clinically relevant ABL kinase mutations respond to change in TKI therapy following imatinib failure, with the majority of patients achieving durable cytogenetic and molecular responses.…”
Section: How To Proceed To Manage CML Disease After Multi-tki Failure?mentioning
confidence: 99%
“…A threonine‐to‐isoleucine substitution at position 315 (T315I mutation), the gatekeeper residue of the Abelson murine leukemia viral oncogene homolog (ABL) kinase domain, is identified in approximately 20% of patients with resistant or relapsed CML3, 4 and confers resistance to most TKIs indicated for CML treatment, such as imatinib, dasatinib, bosutinib, and nilotinib 5. Ponatinib is approved in the United States and the European Union for adult patients with refractory CML or Ph+ ALL and those with the BCR‐ABL T315I mutation, and is now the only effective TKI for treating CML or Ph+ ALL in T315I‐positive patients 3, 4, 6. Recently, it was demonstrated that omacetaxine mepesuccinate, a first‐in‐class cephalotaxine, also has inhibitory activity in TKI‐resistant CML stem cells and provides a benefit to patients who have T315I‐positive chronic phase (CP)‐CML as a single agent or in combination with a TKI 7.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, finding bio markers of CML progression can help in timely therapeutic interventions to minimize drug resistance, treatment failures and relapses, subsequently reducing morbidities and mortalities associated with CML, significantly. 4 Mutations in BCR-ABL1 gene have been found to be a major cause of disease progression and resistance to tyrosine kinase inhibitors in CML patients. [5][6][7] Therefore BCR-ABL mutation detection using capillary sequencing remains to be a gold standard for CML patients exhibiting disease progression and/or drug resistance in European and North American guidelines.…”
Section: Introductionmentioning
confidence: 99%